Subversion de la langue portugaise dans la traduction brésilienne du classique féministe Our Bodies, Ourselves - Érica Lima; Janine Pimentel (Glad!)
This paper presents the project of translating and adapting the feminist book about sexuality and women’s health called Our Bodies, Ourselves into Brazilian Portuguese. The project started in 2019 and the translation-adaptation was published in 2023 under the title Nossos corpos por nós mesmas. By means of examples translated passages in English, Portuguese, and French, we explain why we decided to adopt an inclusive and feminist language in the translation. Examples of the adaptation, in which relevant content for the Brazilian context was created, are also discussed. As both the translation and adaptation processes were challenging in different ways, we reflect on the power play that we felt during the project and conclude that developing projects like this one is, nevertheless, key for the people involved in it, and, most importantly, for society in general.